Hifting Traditions They were as a Social Exchange for the Garojou Community - Jailan, Putri Nurdiana; Hasim, Iksan (Peneliti.net, 2024)
The aim of this research is to describe how Tradition is applied They were as a social exchange in the Garojou community, apart from that, it is also to find out the factors causing the shift in tradition They were the. The method used in this research is qualitative. The aim of using this method is to dig up as much information as possible related to the research problem from figures who are considered to have relevance to provide information related to the research focus. They were is a tradition handed down by the ancestors of the Garojou people, whose implementation as a social exchange has experienced a very significant shift. This shift is caused by polarization at every political moment, and urgent economic incentives that require a decrease in community participation in implementing traditions. they were.